Development of Digital Learning Media Oriented to Realistic Mathematics Education to Improve Students' Independent Learning - Kiki Tristiawanti Simbolon; Zul Amry; Edi Syahputrra (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to produce digital learning tools using a realistic mathematical approach. The type of research used is development research using a modified 4-D development model. XI MIA-1 and XI MIA-2 with 20 students each at SMA Yapim Taruna Marelan. From the results of the first and second trials, it was obtained: The increase in students' learning independence in the geometry transformation material obtained from the average of all I to II trials was 8.20.Keywords: Digital Learning Tool, 4D Model, Independent Learning